The impact of UN high-level meetings on non-communicable disease funding and policy implementation - Svetlana Akselrod; Téa E Collins; Luke N Allen; Amy Collins; Daria Berlina (BMJ Global Health)
Since the original UN General Assembly ‘special session’ for HIV/AIDS, there has been a proliferation of health-related high-level meetings (HLMs), including three for non-communicable diseases (NCDs) and a 2019 HLM on universal health coverage that was closely aligned to the NCD framework. This paper attempts to assess the impact of these meetings in terms of funding allocations, domestic NCD policy implementation, as well as the level of international engagement with the HLMs by reviewing attendance data and records of statements (‘interventions’) made by country delegations. In contrast to HIV/AIDS, whilst NCDs have enjoyed a marked rise in international political exposure and high-level political commitments, these have not always translated into national policy implementation or greater funding allocations. This is true even for countries that have engaged most deeply with HLMs. These findings should give pause to NCD advocacy groups that expend substantial energy in calling for further high-level political commitments and highlight the need to focus support on the translation of commitments into sustainably funded action.